Eagle Station - Brown, Dale, 1956- (New York, NY : William Morrow, an imprint of HarperCollins Publishers, 2020)
"Russia and China have teamed up to gain dominance in outer space, and it's up to McLanahan and the newly formed U.S. Space Force to stop them"--
Keywords: Space weapons -- Fiction; Special operations (Military Science) -- Fiction; McLanahan, Patrick (Fictitious character) -- Fiction; Thrillers (Fiction); Action and adventure fiction